IBM FlashSystem 7300 product guide - Larsen, Carsten; Lottering, Corne; Terwisga, Douwe van; Lonzer, Hartmut; Herd, Jon; Williams, Kendall; Trojok, Konrad; Mookerjee, Shu; Gucer, Vasfi (IBM Redbooks, 2022)
This IBM® Redpaper Product Guide describes the IBM FlashSystem® 7300 solution, which is a next-generation IBM FlashSystem control enclosure. It combines the performance of flash and a Non-Volatile Memory Express (NVMe)-optimized architecture with the reliability and innovation of IBM FlashCore® technology and the rich feature set and high availability (HA) of IBM Spectrum® Virtualize. To take advantage of artificial intelligence (AI)-enhanced applications, real-time big data analytics, and cloud architectures that require higher levels of system performance and storage capacity, enterprises around the globe are rapidly moving to modernize established IT infrastructures. However, for many organizations, staff resources, and expertise are limited, and cost-efficiency is a top priority. These organizations have important investments in existing infrastructure that they want to maximize. They need enterprise-grade solutions that optimize cost-efficiency while simplifying the pathway to modernization. IBM FlashSystem 7300 is designed specifically for these requirements and use cases. It also delivers a cyber resilience without compromising application performance.
Keywords: Computer storage devices; Information storage and retrieval systems; Database management; Information technology -- Management; Ordinateurs; Mémoires; Systèmes d'information; Bases de données; Gestion; Technologie de l'information; Gestion; Information technology; Management